Analytical studies of seized drugs for forensic identification - Rashid, Abdul Rahman Abdul (Universiti Sains Malaysia, 2015)
Drug problems in Malaysia seem to be on the increase despite harsh penalties for those caught supplying the drugs. One of the growing popular drug is methamphetamine and amphetamine. In 2010 seizures of this substance were the highest based on the record (Rehabilitation, 2015). Data from the National Anti-Drugs Agency (NADA) reveals that in total of 150,487 new users are recorded over the period of 12 years with average of 12,540 new cases each year. The total number of new drug users and repeat offenders treated by this agency over the period is 302,472. It is very important to identify seized drug for classification of drug abuse. In this research, 22 samples were used to study on screening test (colour test) and quantitation test (GC-MS). The colour test performed using eight reagents (Marquis, Liebermann’s, Simon, Cobalt Thiocyanate, Froehde’s Sodium Nitroprusside, Janovsky and Chen reagent). For confirmatory examination, GC-MS was used. The result shows that the colour test using eight different reagents has helped to narrow down and provide lead to the possible type of controlled substances present in the 22 questioned samples tested. GC-MS analysis provides useful information on the identity of active compound present in the 22 samples with 5 samples contain only a single compound while the rest consist of mixture of active ingredients and adulterants as well as other impurities. As a conclusion, the colour screening test and GCMS analysis provide a good analytical scheme for routine drug analysis.